PENGARUH BEBAN PAJAK TANGGUHAN, BEBAN PAJAK KINI, DAN KOMPENSASI MANAJEMEN TERHADAP MANAJEMEN LABA (Studi Empiris Pada Bank dan Lembaga Keuangan yang Terdaftar di BEI 2010-2013) - Vincent Junery; R. Adri Satriawan; Rheny Afriana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This research aims to know the effect of deferred tax expense, current tax expense, and management compensation to earnings management according to empiric way. This research did on 19 (nineteen) banks and financial institutions listed in Bursa Efek Indonesia with periodic supervision on 2010-2013. This research is done with purposive sampling method to get representative sample suitable with already done criteria. As to use outliers test to throw away sample with extreme value. Data analyze is used double regression test analyze with classic assumption test composed of normality test, heteroskedatisity test, autocorrelation test, and multi collinearity test. Hypothesis test is done with t test. The result of this research showed that deferred tax expense and current tax expense have significant effect to earnings management, exactly management compensation haven’t significant effect to earnings management.Keywords: Deferred Tax Expense, Current Tax Expense, Management Compensation, and Discretionary Accruals.